Assessment of Adnexal Masses by Transvaginal Sonography and Serum CA125 Assay in Pre- and Postmenopausal Women - Banu, Selina Akhter; Khatun, Sabera; Shamsuddin, Latifa (Bangladesh Journal of Obstetrics & Gynaecology, 2011)
Objective: To compare the diagnostic accuracy of transvaginal sonography and serum CA125 assay for a clinical diagnosis of malignant nature of adnexal masses. Materials and methods: This prospective study was carried out in the department of Obstetrics and Gynaecology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, during the period of January 2001 to December 2002. The study included 86 patients scheduled for laparotomy for an adnexal mass. Among them, 56 patients were pre- menopausal and 30 were postmenopausal. Adnexal masses had been diagnosed by bimanual pelvic examination and by both transabdominal and transvaginal sonography before planning surgery. Results: Considering separately the women with benign or malignant masses, the sensitivity and specificity of transvaginal sonography for the diagnosis of malignant ovarian condition in premenopausal women were 80% and 96.08% and in postmenopausal women these were 60% and 80%, positive and negative predictive values in premenopausal women were 66.67% and 98.00%, whereas in postmenopausal women those were 60% and 80%. Therefore the sensitivity, specificity, positive and negative predictive values of transvaginal sonography in premenopausal women were higher than in postmenopausal women. The diagnostic accuracy of transvaginal sonography in premenopausal women was 94.64% and in postmenopausal women was 73.33%. The sensitivity, specificity, positive predictive value and the diagnostic accuracy of serum CA125 for the diagnosis of malignant ovarian condition in postmenopausal women were higher than premenopausal women. But the negative predictive value in premenopausal women was higher 94.87% than in postmenopausal women 88.90%. Conclusion: Transvaginal sonography used alone is the best method for differentiating between benign and malignant adnexal masses with a good diagnostic accuracy in premenopausal women in addition to clinical symptoms and pelvic examination. The good diagnostic accuracy of transvaginal sonography in premenopausal women may suggest that the addition of further test is not warranted. On the contrary in postmenopausal women, lower diagnostic accuracy of transvaginal sonography may require help of further test to improve it. Keyword: Adnexal mass; Transvaginal sonography; Serum CA125. Bangladesh J Obstet Gynaecol, 2009; Vol. 24(2) : 56-62 DOI: http://dx.doi.org/10.3329/bjog.v24i2.8529